Barriers and facilitators from the patients’ perspective in the follow-up of carpal tunnel syndrome and subacromial impingement syndrome: A qualitative study - Eva Artigues-Barberà; Ester García-Martínez; José María Palacín Peruga; Marta Ortega-Bravo (PLoS ONE, 2026)
Introduction Chronic musculoskeletal pain is one of the leading causes of disability worldwide, affecting 11–50% of the population. In Spain, it accounts for up to 50% of the chronic pain consultations conducted in primary care settings. The most common disorders are carpal tunnel and subacromial impingement syndromes, with treatments, including surgical and nonsurgical approaches, notably the use of ultrasound-guided injections to improve symptoms. Methods A qualitative, phenomenological, and inductive study was conducted on patients diagnosed with carpal tunnel syndrome or subacromial impingement syndrome at primary care centers in Lleida to identify patient‑reported domains relevant to the routine follow-up of CTS and SAIS in primary healthcare, and to examine barriers and facilitators of treatments to inform patient‑centered follow-up protocols. Purposive sampling was used, and five focus groups were organised, selecting participants aged >18 years with or without prior surgical treatment. Data were collected between December 2022 and February 2023 using a semi-structured guide. The focus groups were recorded and thematically analysed using Atlas.ti. Results Twenty-one patients aged between 44–75 years, predominantly women, participated in the study. The results were organised into six themes and 12 subthemes. The barriers identified were delays in diagnostic testing, overload of healthcare personnel, lack of coordination between care levels, and brevity of consultations. Effective communication, empathy of primary care professionals, and prompt management of treatments, such as injections, were highlighted as facilitators. Conclusion This study highlighted the complexity of managing chronic musculoskeletal pain and the need for a multidimensional approach. The identified barriers, along with facilitators, such as effective communication and empathy of professionals, emphasize the relevance of strengthening problem-solving capacity in primary care and fostering better coordination between care levels. These findings suggest that addressing these aspects may support more tailored follow-up and contribute to improving patients’ experiences of care.